Intra- and Post-match Time-Course of Indicators Related to Perceived and Performance Fatigability and Recovery in Elite Youth Soccer Players - Kunz, Philipp; Zinner, Christoph; Holmberg, Hans-Christer; Sperlich, Billy (Frontiers in Physiology, 2019)
Our aims were to examine i) the internal load during simulated soccer match-play by elite youth players; and ii) the time-course of subsequent recovery from perceived and performance fatigability. Eleven male youth players (16 ± 1 yrs, 178 ± 7 cm, 67 ± 7 kg) participated in a 2x40-min simulated soccer match, completing 30 rounds (160 s each) with every round including multidirectional and linear sprinting (LS20m), jumping (CMJ) and running at different intensities. During each round, LS20m, CMJ, agility, heart rate (HR), oxygen uptake (VO2), energy expenditure (EE), substrate utilization and perceived exertion RPE were assessed. In addition, the blood levels of lactate (Lac) was obtained after each of the five rounds. Creatine kinase (CK) concentration, maximal voluntary isometric knee extension and flexion, CMJ, number of skippings in 30 s, and subjective ratings of Acute Recovery and Stress Scale (ARSS) were examined before, and immediately, 24 and 48 h after the simulation. During the game %HRpeak (p<0.05, d=1.08), %VO2peak (p<0.05; d=0.68), Lac (p<0.05, d=2.59), RPEtotal (p<0.05, d=4.59) and RPElegs (p<0.05, d=4.45) all increased with time during both halves (all p<0.05). Agility improved (p<0.05, d=0.70) over the time-course of the game, with no changes in LS20m (p≥0.05, d=0.34) or CMJ (p≥0.05, d=0.27). EE was similar during both halves (528±58 vs 514±61 kcal; p=0.60; d=0.23), with 62% (second half: 65%) carbohydrate, 9% (9%) protein and 26% (27%) fat utilization. With respect to recovery, maximal voluntary knee flexion (p≥0.05, d=0.19) and CMJ (p≥0.05, d=0.13) remained unaltered 24 and 48h after the game. However, effect size calculation revealed the number of skippings during 30 s was lower immediately after the simulated match (p≥0.05, d=0.57) and maximal voluntary knee extension force was lower immediately after the simulation compared to 24h after (p≥0.05, d=0.50). Most ARSS dimensions of load (p<0.05, d=3.79) and recovery (p<0.05, d=3.22) returned to baseline levels after 24 h of recovery. Relative to baseline values, CK was elevated immediately and 24 h after (p<0.05, d=2.03) and normalized 48 h later. In youth soccer players the simulated match evoked considerable circulatory, metabolic and perceptual load, with an EE of 1042±118 kcal. Among the